Anonymity in the Action of Cyber Bullying - Ni Putu Sri Widiasih (Universitas Muhammadiyah Sidoarjo, 2019)
The emergence of cyber bullying is caused by the advancement of information technology that has led to various social networking sites that have an impact on increasing usage internet which leads to violations of social norms. This study aims to identify the role of an anonymous account in criminal acts of cyber bullying, and how to avoid it. The method using in this research is conceptual approach. The characteristics of anonymity in cyber bullying are very important to watch out for, actors in cyber bullying who use anonymous accounts are very difficult to detect, so cyber bullying becomes very dangerous if left unchecked. The result of this study shown, that the anonymity only want to be treated the same or also conceal their identities because they want the forum to only look at what they wrote, not who wrote it. Concealment of identity is done intentionally, but with different reasons. Anonymity becomes very dangerous if used by parties who are not responsible for doing the crime. The role of anonymity in cyber bullying is used by actors to protect their true identities in smoothing out their crimes. Legal protection against anonymity can be done, Indonesia is a rule by law that protects its citizens from the state and citizens other.